Workplace Support For Breastfeeding Mothers In Indonesia : A Scooping Review - Rahmita, Hirza; Fitria, Nurhidaya; Mardiya, Rizka (Journal of Global Research in Public Health, 2023)
The previous research mentioned that returning to work is one of the most common reasons mothers stop breastfeeding. Globally, about 51% of women are involved in the workforce, compared to 82% of men. Attempts to continue breastfeeding at work encounters several difficulties. Workplace support is an effort to increase the coverage of exclusive breastfeeding for working mothers. This scoping review used Arksey and O’Malley framerowk which consisted of 5 stages such as identifying research question, identifying relevant articles, selecting the articles, making data chart and arrange them, summarizing and reporting the research result. Using web covidence application for selecting 183 relevant articles until 11 articles left to be reviewed. This scooping review results mapped three themes such as dimension of workplace support, breastfeeding problems in workplace, and factors that influence the success of exclusive breastfeeding. Working mothers who continue to breastfeed after returning to work need the support of their workplace to ensure the provision of health facilities and the protection and dissemination the rights of breastfeeding working mothers.